Услышь меня, чистый сердцем - Малявина Валентина Александровна (Мемуары, 2000)
Экземпляры: ф.6 (20171221) / Инвентарный номер: 2134 / Цена: / Сис.шифр: 85.37 / Авт.знак: М 21 / ГРНТИ: 18.67 / ББК: 85.374(2)